Prevalence of hepatitis G virus and characterization of viral genome in Ghana. - Saito, T.; Ishikawa, K.; Osei-Kwasi, M.; Kaneko, T.; Brandful, J.A.M.; Nuvor, V.; Aidoo, S.; Ampofo, W.; Apeagyei, F.A.; Ansah, J.E.; Adu-Sarkodie, Y.; Nkrumah, F.K.; et al. (Hepatology Research, 1999)
The prevalence of hepatitis G virus (HGV) infection was investigated in 85 human immunodeficiency virus (HIV)-infected and 30 uninfected individuals' sera obtained from Ghanaians. HGV RNA in serum was identified by a nested reverse transcription polymerase chain reaction (RT-PCR) using primers derived from the 5′-noncoding region. We also tested for hepatitis C virus by nested RT-PCR and for hepatitis B surface antigen (HBsAg) by passive hemagglutination method. HGV RNA was detected in 17 of 85 (20%) HIV sero-positive and three of 30 (10%) sero-negative Ghanaians, respectively. The prevalence of HGV infection was much greater than hepatitis C (0.9%) and hepatitis B virus (7.8%) infections in the present study. Ninety four percent of HGV infected patients were seronegative for hepatitis B and C virus infections. The nine different Ghanaian isolates in the 5′-untranslated region of the HGV genome had one nucleotide deletion at the same position when compared with other HGV isolates. Phylogenetic analysis showed that all Ghanaian isolates belonged to type 1 (West Africa type) of the HGV genotypes. Moreover, we determined nearly full-length nucleotide sequence of the HGV genome (denoted HGV-GA128) recovered from a Ghanaian infected with HIV. The HGV-GA128 was composed of 9231 nucleotides and had a single open reading frame, encoding 2843 amino acid residues. This isolate differed from previously reported HGV/GBV-C isolates by 10–15% of the nucleotide sequence and 2–5% of the amino acid sequence. Our data indicate a high prevalence of HGV, especially genotype 1, in Ghana.
Keywords: Full-length sequence of Ghanaian HGV isolate (HGV-GA128); Ghana; Hepatitis G virus (HGV) genome; HGV genotypes